2020
DOI: 10.1002/zaac.202000290
|View full text |Cite
|
Sign up to set email alerts
|

Metal ions Directed Self‐assembly based on Mixed Ligands: From 2D hcb Net to 3D cds Framework

Abstract: Two coordination polymers (CPs), namely, [Zn(BPDC)(3bpdb) 0.5 (H 2 O) 2 ] n (1), and [Ni(BPDC)(3-bpdb)(H 2 O) 2 ] n (2) (where H 2 BPDC = 4,4'-biphenyldicarboxylic acid, 3-bpdb = 1,4-bis(3-pyridyl)-2,3-diaza-1,3-butadiene) have been solvothermally synthesized and characterized by single-crystal X-ray diffraction, IR, elemental analyses, PXRD, and SEM. CP 1 possesses a 2D 3-connected hcb net, and weak hydrogen bonding and π•••π stacking contacts further link the 2D networks to form 3D supramolecular structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In our previous studies on the construction of bpdb/polycarboxylate mixed-ligands CPs, we found that metal ions have a strong regulatory effect on the skeleton of the frameworks. 50 In order to confirm the regulation roles of the substituents on the skeleton, and to determine whether metal ions or other factors also can affect the frameworks in this series of CPs, cobalt nitrate was selected as metal salts to react with 3-bpdb and 5-substituted isophthalic acid ligands with similar reactions with 1−4, and four Co(II)-based CPs were obtained (7−10). Single-crystal X-ray diffraction analysis revealed that the all the Co(II) ions in 7−10 are six coordinated in distorted octahedral coordination spheres with σ values of 0.647, 0.620, 0.636, and 0.620, respectively (Scheme S1).…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies on the construction of bpdb/polycarboxylate mixed-ligands CPs, we found that metal ions have a strong regulatory effect on the skeleton of the frameworks. 50 In order to confirm the regulation roles of the substituents on the skeleton, and to determine whether metal ions or other factors also can affect the frameworks in this series of CPs, cobalt nitrate was selected as metal salts to react with 3-bpdb and 5-substituted isophthalic acid ligands with similar reactions with 1−4, and four Co(II)-based CPs were obtained (7−10). Single-crystal X-ray diffraction analysis revealed that the all the Co(II) ions in 7−10 are six coordinated in distorted octahedral coordination spheres with σ values of 0.647, 0.620, 0.636, and 0.620, respectively (Scheme S1).…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…As shown in Figure S5, there is an emission peak with maxima at 394 nm and a shoulder peak at 469 nm (λ ex = 254 nm) for 3-bpdb, which is consistent with that previously reported. 50 For carboxylic acid ligands, the best emission peaks of MeO-H 2 ip, EtO-H 2 ip, and n-PrO-H 2 ip are at 358, 361, and 363 nm (λ ex = 315 nm) respectively, and the best emission of n-BuO-H 2 ip is at 416 nm (λ ex = 345 nm) (Figure S6). These emissions may be due to the intraligand π* → n or π* → π transitions.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%